Nivel de satisfacción percibida por los pacientes adultos con quemaduras y la calidad del cuidado de enfermería Hospital Belén de Trujillo Febrero 2010 - Campos Ulloa, Grecia Isabel (2010)
The present work of investigation of descriptive type correlate, with quantitative boarding, carried out in the services of Surgery To and B of the Hospital Bethlehem of Trujillo, with the intention of investigating the relation between the level of satisfaction perceived by the adult patients with burns and the quality of the care of infirmary. For the compilation of information there was in use two instruments "Level of Satisfaction perceived by the patient" and "Quality of the Care of Infirmary" which was applied to 30 adult patients by burns in February, 2010. For the statistical analysis the program was in use Microsoft Scullery 2007. On having analyzed the results there was obtained that they are satisfied 56.7 per cent of the patients and 43.3 per cent unsatisfied. 66.7 per cent of the patients they receive a quality of the care of regular infirmary, 16.7 per cent a quality of the inadequate care of infirmary and the same suitable percentage. Of 100 per cent of the adult patients with burns that receive a quality of the care of regular infirmary, 60 per cent they are unsatisfied and 40 per cent they perceive to be satisfied. One concludes that there exists a statistical significant relation between the level of satisfaction perceived by the adult patients with burns and the quality of the care of infirmary (p = 0.0027).